The Effectiveness of Hypothetical Learning Trajectory on Quadrilateral Topics for Junior High School Students - Amelia, Risma; Herman, Tatang ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Geometry is an essential topic things to needs to be mastered by participants, one of the topics on geometry is quadrilateral. However, in conditions in the field students Still have difficulty understanding quadrilateral topics. Research This aims to design Hypothetical Learning Trajectory (HLT) Quadrilateral Topics for Grade VII Junior High School Students according to with needs of students and appropriate with the process of thinking student with analyze the effectiveness of HLT applied. The method used in the study This is method design research consisting of three stages : (1) preparation experiment to design HLT (2) design experiment that implements HLT which has been designed, and (3) analysis retrospective that analyzes effectiveness HLT applied in learning. Deep data collection techniques study this : (1) Interviews with teachers and students, (2) Observation and observation, and (3) Documentation For analysis and clarifying HLT. Subject study This consists of 20 students of SMPN 2 Cimahi Class VII with characteristics of heterogeneous students with high, medium, and low ability. This article serves results at stage preparation experiment, design experiments, and analysis retrospective as well as analyze HLT material effectiveness quadrilateral. Track design Study includes, objectives learning material quadrilateral, activities and tasks designed learning For material quadrilateral, and hypothesis channel think a student in understanding draft material quadrilateral. The study This produced HLT which consists of a series of activity learning material rectangle on indicator understand properties quadrilateral, and find around quadrilateral. Analysis results show that HLT is designed in study This Still needs development For activities on the topic properties square, but gives change positive to student class VII in understanding draft around quadrilateral. Analysis results effectiveness reviewed from completeness Study produced by 85% of studes Already achieve KKM on the material quadrilateral, thing This show that the HLT was designed Already effective applied in learning.